2022
DOI: 10.3389/fpsyg.2022.799103
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Effects of “Mindfulness Acceptance Insight Commitment” Training on Flow State and Mental Health of College Swimmers: A Randomized Controlled Experimental Study

Abstract: This research explores the intervention effect of the mindfulness acceptance insight commitment (MAIC) training program on the mindfulness level, flow state, and mental health of college swimmers. A sample of 47 college swimmers from a regular university was recruited and randomly divided into two groups before the intervention. Independent variables between groups are psychological training mode (MAIC training/no training), and the independent variable within group was time (pre-test, post-test, and continuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Practicing yoga that connects the mind and body and regulates arousal could lighten the burden of stress and anxiety disorders [ 42 ]. The present study consistently reported significant results with several studies [ 20 , 22 , 30 , 31 , 42 ]. A meta-analysis of nine experimental trials observed that mindfulness practice constantly regulates mindfulness scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Practicing yoga that connects the mind and body and regulates arousal could lighten the burden of stress and anxiety disorders [ 42 ]. The present study consistently reported significant results with several studies [ 20 , 22 , 30 , 31 , 42 ]. A meta-analysis of nine experimental trials observed that mindfulness practice constantly regulates mindfulness scores.…”
Section: Discussionsupporting
confidence: 92%
“… First author and year of the study Study design Setting Participants' Intervention/Control Participant's Age Mean (S.D.) Intervention Comparison Outcomes Goodman 2014 [ 20 ] RCT Participants were African, American, Caucasian, and other 13/13 Intervention group; 20.23 (1.53) 90-min group intervention sessions immediately followed by 1-hr Hatha yoga sessions- 5 Weeks Control group Acceptance and Action Questionnaire Version–II (Experiential avoidance) Mindful Attention and Awareness Scale Perceived Stress Scale Dehghani M, 2018 [ 21 ] RCT Iran 15/16 Intervention group; 23.44 (0.49) years/control group; 22.34 (0.34) years Mindfulness-Acceptance-Commitment (MAC) for eight sessions Control group Action and Acceptance Questionnaire (AAQ) Ning, 2022 [ 22 ] RCT China 24/24 Intervention group; 22.34 (2.17) years Psychological training mode (MAIC training) Control group Five Facet Mindfulness Questionnaire Competitive State Anxiety Inventory Flow state scale Liang, 2021 [ 23 ] RCT China 14/10 Intervention group; 20.85 (1.46)/control group; 21 (1.16) 30-min -convenient progressive relaxation training (PRT)- 4 Weeks Control group Competitive State Anxiety Inventory Mehrsafar, 2019 [ 24 ] RCT Iran 13/13 Intervention group:M = 24.6, (2.5) years, control group: 26.2, (2.3) years An 8-week Mindfulness-based intervention Control group Competitive State Anxiety Inventory Scott–Hamilton, 2016 [ 25 ] RCT Australia 27/20 Intervention group: 38.96, (12.4)/Control group:40.65, (10.88) Eight-week mindfulness meditation intervention Control group Five facet mindfulness questionnaires ...…”
Section: Study Selection As Per the Pico Frameworkmentioning
confidence: 99%
“…Many studies and reviews have emphasised the importance of these factors for improving performance [ 52 , 53 , 54 ]. Athletes with more self-confidence are more likely to see anxiety as a functional sign and use it to improve their performance [ 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…College students’ levels of anxiety and depression can be reduced by mindfulness practice, which is widely used to control emotions and relieve stress [ 59 , 60 , 61 ]. Additionally, acceptance-based intervention techniques are used to raise athletes’ performance levels, demonstrating the value of improving athletes’ flow state experiences in the context of sports [ 57 , 62 , 63 , 64 ]. Furthermore, mindfulness training might enhance athletes’ sporting experiences while also providing psychological benefits [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of follow-up MAIC intervention studies targeting athletes of dart throwing, shooting sports, and swimming showed that MAIC training could significantly improve their psychological outcomes (mindfulness, acceptance, flow state, anxiety reduction, training, competition satisfaction, etc.) as well as their athletic performance [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%